An exploratory investigation of superstitious behaviours, coping, control strategies, and personal control in Ghanaian and British student-athletes. Issue 1 (2nd January 2018) - Ofori, Patrick Kwaku; Tod, David; Lavallee, David
Abstract : This study examined the relationships between primary and secondary control strategies, coping, and superstitious behaviour. Participants were 349 student-athletes from the UK and Ghana, consisting of 194 males and 155 females. The nationality breakdown was 177 British student-athletes and 172 Ghanaian student-athletes. Participants completed five inventories measuring superstitious behaviours, personal control, control strategies, coping skills, and social desirability. Sequential multiple regression analysis was used to determine the relationship between these constructs. A 2 by 2 analysis of covariance was conducted to assess the main and interactive effects of gender and nationality on superstitious behaviour. Findings demonstrated that personal control, coping mechanisms, and control strategies predicted superstitious behaviour. The findings suggest that athletes may engage in superstitious behaviour as a coping mechanism and as a secondary control strategy to offer them a sense of being in control in stressful situations. The results suggest that Ghanaian student-athletes may engage in superstitious behaviour more than British student-athletes. Results are discussed in relation to previous research and practical implications are delineated.